Correlation of Ankle - Brachial Index (ABI) and Low - Density Lipoprotein (LDL) with Diabetic Foot Severity Degree - Muhammad Ghaly Maulana; Nanang Miftah Fajari; Dewi Indah Noviana Pratiwi (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: Diabetic foot is a complication of diabetes mellitus which is characterized by ulceration in the legs. The severity of the diabetic foot can be determined by the Wagner-Meggit system which in this study uses 5 categories namely degrees 1 - 5 degrees. ABI (Ankle-Brachial Index) is an evaluation of peripheral arterial disease in diabetic foot patients. LDL is the main factor of atherosclerosis which causes macrovascular disorders in diabetic foot. The purpose of this study was to determine the correlation between ABI and LDL on the severity of diabetic foot based on the Wagner-Meggit classification. The method used is observational analytic with cross sectional approach. A total of 35 samples were obtained by consecutive sampling. Data analysis was performed using the Spearman test and logistic regression. A significant correlation was obtained between ABI and the severity of diabetic foot (p = 0.06; r = -0.424), there was no correlation between LDL and the severity of diabetic foot (p = 0.09; r = -0.395). The results of logistic regression analysis found no correlation between ABI (p = 0.163; OR = 0.008) and LDL (p = 0.69; OR = 0.984) with the severity of the diabetic foot. Obtained Negelkerke R Square value of 0.095. Keywords: Diabetic foot, ABI, LDL, Wagner-Meggit classification